Mortality Reporting Modeling in Healthcare Facilities in Indonesia - Rusdi, Achmad Jaelani; Suhariyono, Untung Slamet (Universitas Muhammadiyah Sidoarjo, 2024)
Healthcare facilities in Indonesia, such as hospitals and public health centers, play a crucial role in recording and reporting mortality data necessary for health policy development and quality assessment. Although various reporting methods are available, ranging from manual to electronic systems, the primary focus has often been on morbidity rather than mortality. External reporting processes typically involve basic coding for morbidity and mortality, and the application of the International Classification of Diseases (ICD) for cause-of-death determination in electronic medical records is still underdeveloped. This study employs a qualitative descriptive approach with a system modeling framework to design a comprehensive mortality reporting model that incorporates data mining techniques. By analyzing secondary data from integrated mortality reporting systems in Indonesian healthcare facilities, the study proposes a model that enhances data processing and presentation, offering a structured approach for utilizing mortality data for policy development and future forecasting. The results demonstrate that this model significantly improves data management processes and provides a valuable framework for advancing health policy. Future research should explore the implementation of this model and assess its impact on health policy outcomes in Indonesia.